Enhancing Student Engagement in Qur'anic Learning through Peer Tutoring: Evidence from Islamic Religious Education Classrooms - Salma Fuji A (DAAR EL-KAMIL: Multidisciplinary Journal, 2026)
This study is motivated by the low level of student participation in learning the Qur'an in Islamic Religious Education (PAI) subjects in class VII at A MTs Daarul Ihsaan Cimahi. This condition is indicated by the lack of student activeness in reading, asking questions, and interacting during the learning process. This study aims to describe the implementation of the peer tutoring method and to determine the improvement of student participation in learning the Qur'an. The method used in this research is Classroom Action Research (CAR) with the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages conducted in two cycles. The subjects of this study were seventh-grade students of MTs Daarul Ihsaan Cimahi, totaling 28 students. Data collection techniques included observation, interviews, and documentation. Data were analyzed using descriptive qualitative analysis through data reduction, data display, and conclusion drawing. The results showed that the implementation of the peer tutoring method significantly improved student participation in learning the Qur'an, as indicated by increased student activeness in reading, asking questions, discussing, and engaging in group activities. In Cycle I, student participation reached 62%, and in Cycle II it increased to 85%, exceeding the predetermined success indicator of 75%. Therefore, the peer tutoring method can be an effective alternative in improving the quality of PAI learning, especially in Qur'anic learning.